Cases of Acute Abdomen Radiography With Perforation At General Hospital Haji Adam Malik: Cases of Acute Abdomen Radiography With Perforation At General Hospital Haji Adam Malik - Nita Triana Saragih; Nelida Pasaribu; Helvinus Laia (Journal of Midwifery and Nursing, 2020)
This examination is discussed on the level of success in doing Techniques Radiography Acute Abdomen By Case Perforations, data was obtained by firstly be the Formation of Shadows with menggnakan Computed Radiography, Aircraft X-ray used is a plane general X-ray unit, with the projection used is Antero-posterior supine, Antero-posterior erect, and Left Lateral Decubitus, on examination Abdomen Perforation Wide Field irradiation should be tailored to the size of the object to reduce the radiation scattering, and use the grid to absorb radiation hamburg and reduce the radiation dose, Placement Marker should be on the object to be photographed , These checks are carried out directly and relate to patients.